2010
DOI: 10.1111/j.1399-3062.2010.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of respiratory syncytial virus infection in adult patients with hematologic malignancies based on an institution‐specific guideline

Abstract: A total of 26 adults with hematologic malignancies and/or hematopoietic stem cell transplant were treated for respiratory syncytial virus (RSV) infection based on an institutional guideline. Thirteen patients received aerosolized ribavirin, and 13 received aerosolized ribavirin and intravenous palivizumab. Two deaths, not attributed to RSV infection, occurred within 90 days of diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…No adverse events were reported related to palivizumab 17. A survey of current practices among the International Pediatric Lung Transplant Collaborative was published in 2012 18. This survey revealed that of the 15 centers who responded to questions regarding treatment strategies, six centers reported using palivizumab (three IV, three intramuscular).…”
Section: Preventative/vaccinationmentioning
confidence: 99%
See 4 more Smart Citations
“…No adverse events were reported related to palivizumab 17. A survey of current practices among the International Pediatric Lung Transplant Collaborative was published in 2012 18. This survey revealed that of the 15 centers who responded to questions regarding treatment strategies, six centers reported using palivizumab (three IV, three intramuscular).…”
Section: Preventative/vaccinationmentioning
confidence: 99%
“…This survey revealed that of the 15 centers who responded to questions regarding treatment strategies, six centers reported using palivizumab (three IV, three intramuscular). The dose reported by all centers was 15 mg/kg over the course of one day (intramuscular) or up to three days (IV) 18. In adult populations, some data has also been published with regard to the utility of palivizumab in the setting of acute RSV infection 19.…”
Section: Preventative/vaccinationmentioning
confidence: 99%
See 3 more Smart Citations